King Island Eskimos in the surf landing their umiak on the beach, Nome, Alaska, 1900 - Hester, Wilhelm, 1872-1947 (1900)
Caption on image: King Island Eskimos making a landing in their skin canoe on Nome beach Alaska, Copyrighted by W. Hester, Seattle, 1900. No. 210 appears in lower left hand corner of image. PH Coll 318.1025 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number